Comparison of Bird Diversity Across different Landscapes in Thar Desert of Rajasthan, India - Bhardwaj, Gobind Sagar (Indian Forester, 2020)
The bird survey of some parts of Thar desert in western part of Rajasthan revealed a sighting of 234 species belonging to 59 families among all 16593 of bird observations made during 2014 to 2017. High abundance of Eurasian Collared Dove, Streptopelia decaocto, in all landscapes, especially agro-pastoral areas established its generalist behavior. Maximum bird diversity in small fully protected landscapes like Tal Chaper WLS and enclosures made in human dominated Desert National Park justifies the need ofminimizing the human-wildlife interface through raising physicalbarriers forlong term conservation planning. High occurrence ofcritically endangered Great Indian Bustard, Ardeotis nigriceps, in enclosures ofDesert NationalPark andRamdeora in Thar landscape shows the importance offenced inviolate areas for the in situ conservation plans forth e species.